Dental Management of Ectodermal dysplasia: A case report - Singh, Baljeet; Kaur, Harpreet; Joshi, Bharat; Sahira, Sudan (Indian Journal of Case Reports, 2016)
A variety of syndromes/disorders (genetic/acquired) are encountered in our day-to-day life. Among them, ectodermal dysplasia is a rare syndrome which is transmitted as x-linked recessive/dominant disorder and is known to majorly affect males as compared to females. Clinically, it is observed that there is presence of partial or complete anodontia with conical teeth along with maxillary retrusion, prominent supraorbital ridges or frontal bossing, fine and blond, scanty hair (resembling lanuogo), deformed or absent nails, facial physiognomy (fairy-like face) and reduced sweating. Early diagnosis remains the key for the management of ectodermal dysplasia. Since patient suffers from unpleasant appearance (due to partial or complete anodontia); hence, dental management includes replacement of teeth by either fixed/removable partial or complete dentures /implant- supported dentures. We present a case of ectodermal dysplasia with features of oligodontia, severely deficient alveolar processes and maxillary retrusion which was managed with tooth-supported complete overdentures.